2015
DOI: 10.1016/j.semcancer.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Tissue invasion and metastasis: Molecular, biological and clinical perspectives

Abstract: Cancer is a key health issue across the world, causing substantial patient morbidity and mortality. Patient prognosis is tightly linked with metastatic dissemination of the disease to distant sites, with metastatic diseases accounting for a vast percentage of cancer patient mortality. While advances in this area have been made, the process of cancer metastasis and the factors governing cancer spread and establishment at secondary locations is still poorly understood. The current article summarizes recent progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
295
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(319 citation statements)
references
References 501 publications
(305 reference statements)
8
295
0
9
Order By: Relevance
“…Adhesion molecules are strong candidates to be involved in the metastatic spread of melanoma 30. PG, also known as γ‐catenin,31, 32 is a component of adherens junctions and desmosomes, and it plays an important role in Wnt/β‐catenin signaling 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion molecules are strong candidates to be involved in the metastatic spread of melanoma 30. PG, also known as γ‐catenin,31, 32 is a component of adherens junctions and desmosomes, and it plays an important role in Wnt/β‐catenin signaling 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…67 The present data indicate that CTCs in SCLC recruit macrophages through monocyte differentiation with high efficacy. 6 Comparison of the density of monocytes in control HEK293-CM treated PBMNCs with recombinant CHI3L1 exposed cells indicated that most of the monocytes differentiate to macrophages. The HEK293 cell line was selected since it expresses no significant amounts of GM-CSF and G-CSF, in good correspondence with the two CTC lines (R&D cytokine array; data not shown).…”
Section: Secretory Phenotype Of Sclc Ctc-induced Macrophagesmentioning
confidence: 99%
“…5 Thus cancers and, possibly, CTCs recruit immunosuppressive cells, particularly belonging to the myeloidmacrophage lineage, which undergo functional polarization in dependence of tumor-derived factors. 6 These "tumor-educated" macrophages promote invasion, intravasation as well as survival in the circulation and durable growth at secondary lesions. 5,7 TAMs are recruited by various cytokines and chemokines, suppress the activity of cytotoxic T-lymphocytes via programmed cell death 1 ligand 1 (PD-L1) or B7-H4 and other receptors/mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors and, possibly, CTCs educate macrophages to promote invasion, intravasation as well as survival in the circulation and durable growth at secondary lesions (3,29,30). The invasiveness of tumor cells was dramatically enhanced when they were cocultured with macrophages or macrophage conditioned medium (31).…”
Section: Tamsmentioning
confidence: 99%